2018
DOI: 10.1155/2018/3538764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Platelet-Rich Plasma in the Treatment of Neurotrophic Corneal Ulcer

Abstract: Purpose Platelet-rich plasma (PRP) is an autologous blood product without preservatives and rich in proteins and growth factors which make it possible for cells to differentiate, proliferate, and migrate, thus stimulating healing and regeneration of tissues. The aim of this study was to evaluate the efficiency of autologous platelet-rich plasma in the treatment of neurotrophic keratopathy. Methods The study group consists of 25 patients with nonhealing corneal ulcers due to herpes simplex or herpes zoster infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…A complete resolution of corneal ulcer was reported in 97.4% of patients with NK after a mean time of 11.4 weeks [115]. Similar results were obtained in 25 NK patients treated by Wróbel-Dudzinska et al with PRP eye drops, with complete healing of the corneal ulcer observed in 80% of patients, while improved symptoms and visual acuity observed in all of them [118]. In a randomized clinical trial, Garcia-Conca et al compared PRP eye drops with tear substitutes in patients with hyposecretory DED [119].…”
Section: Platelet Derived Eye Dropssupporting
confidence: 59%
“…A complete resolution of corneal ulcer was reported in 97.4% of patients with NK after a mean time of 11.4 weeks [115]. Similar results were obtained in 25 NK patients treated by Wróbel-Dudzinska et al with PRP eye drops, with complete healing of the corneal ulcer observed in 80% of patients, while improved symptoms and visual acuity observed in all of them [118]. In a randomized clinical trial, Garcia-Conca et al compared PRP eye drops with tear substitutes in patients with hyposecretory DED [119].…”
Section: Platelet Derived Eye Dropssupporting
confidence: 59%
“…Interestingly, it is also possible to withdraw an aliquot of the L-PRP obtained from the collection bag in a sterile manner, so as to be able to keep the remainder for dermatological or oculistic periodic therapeutic treatments in the same subject. Shelf life of the remaining product may be prolonged by freezing, as carried is out in human medicine [ 75 , 76 ], though studies demonstrate that freezing is detrimental to platelet morphology and function and continuous synthesis of growth factors [ 36 ]. In veterinary medicine, there are few studies considering extension of the shelf life by freezing of platelet concentrates [ 54 , 77 , 78 , 79 , 80 ] and in the dog there are no literature reports that confirm the best preservation method.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that PRP influences wound healing by stimulating tissue repair mechanisms, enhancing tissue healing and regeneration including bone, cartilage, tendon and muscle at various levels with minimal adverse effects (Albanese et al., 2013; Alsousou et al., 2013; Rah et al., 2017; Lang et al., 2018; Tambella et al., 2018a,b). Indeed, PRP has been used to enhance the healing process of various types of wounds (Kim et al., 2009; Alsousou et al., 2013; Picard et al., 2015; Alishahi et al., 2014; Tambella et al., 2014; Martinez-Zapata et al., 2016; Burgos-Alonso et al., 2018; Tambella et al., 2018a,b; Moneib et al., 2018), orthopaedics (Alsousou et al., 2013; Samy, 2016; Faillace et al., 2017; Marcazzan et al., 2018; Huang et al., 2019), ophthalmology (Ronci et al., 2015; Wróbel-Dudzińska et al., 2018; Alio et al., 2018), and dentistry (Del Fabbro et al., 2017; Tabrizi et al., 2018; Bhujbal et al., 2018; Saleem et al., 2018).…”
Section: Introductionmentioning
confidence: 99%